Effects of gum chewing and repetitive motor activity on sustained attention in adults with attention deficit-hyperactivity disorder. Issue 8 (17th November 2022) - Can, Kazım Cihan; Tugba Ozel-Kizil, Erguvan; Colak, Burcin; Duman, Berker
ABSTRACT: Attention is a cognitive and behavioural process that can be affected by numerous internal and external factors. Gum chewing (GC) and repetitive motor activity (RMA) have previously been associated with improved attention. This study aimed to investigate the effects of GC and RMA on sustained attention in Attention Deficit-Hyperactivity Disorder (ADHD) A modified AX-CPT was applied to all participants (35 adults with ADHD and 30 healthy adults) for three conditions neutral, GC and RMA. There were significant differences between the groups in terms of the target responses for the neutral and the RMA conditions. A 2 (Groups) × 3 (Conditions) ANOVA revealed only a significant condition main effect. In GC and RMA, MRTs were decreased for both groups compared to the neutral condition. Both GC and RMA have improved sustained attention performance, similarly in ADHD and healthy adults so they may be used as easily accessible tools for improving attention.